2021
DOI: 10.3389/fphys.2020.624657
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating the Resolution of Inflammation Through Omega-3 Polyunsaturated Fatty Acids in COVID-19: Rationale for the COVID-Omega-F Trial

Abstract: Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes coronavirus disease 2019 (COVID-19). SARS-CoV-2 triggers an immune response with local inflammation in the lung, which may extend to a systemic hyperinflammatory reaction. Excessive inflammation has been reported in severe cases with respiratory failure and cardiovascular complications. In addition to the release of cytokines, referred to as cytokine release syndrome or “cytokine storm,” increased pro-inflammatory lipid mediator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 47 publications
(48 reference statements)
0
76
1
Order By: Relevance
“…On another level, there is still the question of whether fish oils can raise the levels of SPM levels upon ingestion and in response to acute inflammation in humans ( 63 ). Currently, Karolinska University Hospital is running a trial that will measure the levels of SPM as a secondary outcome following intravenous supplementation of n-3 PUFAs in hospitalized COVID-19 patients to determine whether n-3 PUFAs provide therapeutic value ( 64 , 65 ). Therefore, while this mechanism provides theoretical support for a role for n-3 PUFAs against COVID-19, experimental support is still needed.…”
Section: N-3 Pufamentioning
confidence: 99%
“…On another level, there is still the question of whether fish oils can raise the levels of SPM levels upon ingestion and in response to acute inflammation in humans ( 63 ). Currently, Karolinska University Hospital is running a trial that will measure the levels of SPM as a secondary outcome following intravenous supplementation of n-3 PUFAs in hospitalized COVID-19 patients to determine whether n-3 PUFAs provide therapeutic value ( 64 , 65 ). Therefore, while this mechanism provides theoretical support for a role for n-3 PUFAs against COVID-19, experimental support is still needed.…”
Section: N-3 Pufamentioning
confidence: 99%
“…Thus, increasing omega-3 PUFA and decreasing omega-6 PUFA levels may represent a possible mean to skew the immune response toward resolution of inflammation, which led to the conception of the COVID-Omega-F Trial with the aim of resolving the cytokine storm in COVID-19 patients by supplementation of hospitalized patients with high-dose omega-3 PUFA i.v. over 5 days ( Arnardottir et al, 2021 ), ClinicalTrials.gov Identifier: NCT04647604, estimated study termination date April 30, 2021. However, the situation seems more complex than a simplified omega-3/omega-6 classification would reflect.…”
Section: Bioactive Lipid Mediators In Virus Infection From Influenza Virus To Sars-cov-2mentioning
confidence: 99%
“…While IV emulsions with DHA and EPA were shown to be protective ( Pontes-Arruda and Hirasawa, 2011 ), dietary supplementation with fishoil or with n-3 fatty acids, γ -linolenic acid, and antioxidants did not show a clear benefit in ARDS ( Rice et al, 2011 ; Stapleton et al, 2011 ). On the other hand, independent meta-analyses indicated that supplementation with omega-3 PUFA in patients with ARDS would associate with improvements in the PaO2/FiO2 ratio, with a shorter ICU stay, a shorter duration of mechanical ventilation, and a trend toward reduced mortality ( Dushianthan et al, 2019 ; Langlois et al, 2019 ; Arnardottir et al, 2021 ).…”
Section: Bioactive Lipid Mediators In Virus Infection From Influenza Virus To Sars-cov-2mentioning
confidence: 99%
“…Notably, the inverse associations between the O3I with the outcome variables were observed within a relatively narrow range of O3I values, which strongly suggests that COVID-19 risk stratification based on O3I categories may indeed be feasible [26]. This finding also reinforces the need to include the basal O3I of eligible participants in future randomized clinical trials of Omega-3 fatty acids in COVID-19 [30][31][32]; unbiased research requires valid comparisons, and the predictive value of biomarkers should be validated in well-designed prospective clinical studies. Increasing evidence strongly suggests the omega-6:Omega-3 fatty acid ratio should be replaced by a metric that focuses on the primary deficiency in Western diets-the lack of EPA and DHA [33]; namely, the Omega-3 Index.…”
Section: Discussionmentioning
confidence: 61%